TurnAware: motion-aware Augmented Reality information delivery while walking - Liu, Sunniva; Lindlbauer, David (Frontiers in Virtual Reality, 2024)
Augmented Reality (AR) systems provide users with timely access to everyday information.Designing how AR messages are presented to the user, however, is challenging. If a visual message is presented suddenly in users' field of view, it will be noticed easily, but might be disruptive to users. Conversely, if messages are made visible by slowly fading their opacity, for example, they might require more effort for users to notice and react, as they need to wait for the content to appear. This is particularly true for head-anchored virtual content, and when users are engaged in other tasks or walking in a physical environment. To address this challenge, we introduce a motion-aware technique that delivers AR visual information unobtrusively during walking when users rotate their head. When users make a turn, TurnAware moves the visual content into their field of view from the side at a speed proportional to their rotational velocity. We compare our method to a Fade-in and Pop-up baseline in a user study. Our results show that our method enables users to react to virtual content in a timely manner, while minimizing disruption on their walking patterns. Our technique improves current AR information delivery techniques by striking a balance between noticeability and disruptiveness.